Possible role for rare TRPM7 variants in patients with hypomagnesaemia with secondary hypocalcaemia. Issue 3 (13th May 2022) - Vargas-Poussou, Rosa; Claverie-Martin, Felix; Prot-Bertoye, Caroline; Carotti, Valentina; van der Wijst, Jenny; Perdomo-Ramirez, Ana; Fraga-Rodriguez, Gloria M; Hureaux, Marguerite; Bos, Caro; Latta, Femke; Houillier, Pascal; Hoenderop, Joost G J; et al.
ABSTRACT: Background: Hypomagnesaemia with secondary hypocal-caemia (HSH) is a rare autosomal recessive disorder caused by pathogenic variants in TRPM6, encoding the channel-kinase transient receptor potential melastatin type 6. Patients have very low serum magnesium (Mg 2+ ) levels and suffer from muscle cramps and seizures. Despite genetic testing, a subgroup of HSH patients remains without a diagnosis. Methods: In this study, two families with an HSH phenotype but negative for TRPM6 pathogenic variants were subjected to whole exome sequencing. Using a complementary combination of biochemical and functional analyses in overexpression systems and patient-derived fibroblasts, the effect of the TRPM7 -identified variants on Mg 2+ transport was examined. Results: For the first time, variants in TRPM7 were identified in two families as a potential cause for hereditary HSH. Patients suffer from seizures and muscle cramps due to magnesium deficiency and episodes of hypocalcaemia. In the first family, a splice site variant caused the incorporation of intron 1 sequences into the TRPM7 messenger RNA and generated a premature stop codon. As a consequence, patient-derived fibroblasts exhibit decreased cell growth. In the second family, a heterozygous missense variant in the pore domain resulted in decreased TRPM7 channel activity. Conclusions: We establish TRPM7 as a prime candidate gene for autosomal dominant hypomagnesaemia and secondary hypocalcaemia. Screening of unresolved patients with hypocalcaemia and secondary hypocalcaemia may further establish TRPM7 pathogenic variants as a novel Mendelian disorder. Graphical Abstract: